Identifying barriers to off-site construction using grey DEMATEL approach: case of China - Han, Yanhu; Wang, Lufan (Journal of Civil Engineering and Management, 2018)
Off-site construction (OSC) methods have been widely adopted in the construction industry around the world. However, in a lot of developing countries, the application of OSC still lags behind. Although a number of research efforts have focused on identifying the OSC barriers, they are limited to qualitative descriptions, which lacks the understanding of the interrelationships among the barriers. To address this gap, this paper proposed a methodology for identifying the OSC barriers and their cause-effect relationships. The proposed methodology is composed of three phases: (1) a comprehensive literature review and in-depth interview with the OSC industry experts, (2) questionnaire survey and focus group discussion, and (3) grey DEMATEL analysis. The proposed methodology was applied in the context of China’s construction industry. The results of the grey DEMATEL analysis provided the cause-effect relationships of the 35 identified OSC barriers, which indicated six important aspects be taken into deeper consideration, such as governmental regulations and incentives, OSC practices and experiences, as well as traditional construction method transformation. The outcomes of this study will support policymakers and OSC participants to identify the influencing OSC barriers and their interrelationships, as well as propose appropriate strategies for overcoming the barriers and broadening the OSC application.